Arthroscopic Thermal Capsular Shrinkage for Palmar Midcarpal Instability - Hargreaves, David G. (Journal of Wrist Surgery, 2014)
Background Arthroscopic capsular shrinkage has been previously used to stabilize major joints. This is the first series of its use in the wrist for palmar midcarpal instability (PMCI).Materials and Methods This is a medium-term retrospective review of 13 patients (15 wrists) at an average follow-up of 48 months postoperative. All patients were assessed with a functional questionnaire for instability and a Disabilities of the Arm, Shoulder, and Hand (DASH) score, as well as clinical examination.Description of Technique Arthroscopic capsular shrinkage was performed to the palmar and dorsal capsules of the radiocarpal and midcarpal joints using a bipolar thermal probe. All wrists were immobilized for 6 weeks post operation.Results 100% follow-up was achieved . All cases had an improvement in the frequency and severity of instability symptoms. The average DASH score was significantly reduced. There were no complications. The average loss of movement following the procedure was 15%.Conclusions The medium-term results show that wrist instability due to PMCI can be improved significantly by thermal capsular shrinkage with only a minimal amount of secondary stiffness.
Keywords: wrist arthroscopy; midcarpal instability; capsular shrinkage